If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2h + -26 = 3h + -6 Reorder the terms: -26 + -2h = 3h + -6 Reorder the terms: -26 + -2h = -6 + 3h Solving -26 + -2h = -6 + 3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-3h' to each side of the equation. -26 + -2h + -3h = -6 + 3h + -3h Combine like terms: -2h + -3h = -5h -26 + -5h = -6 + 3h + -3h Combine like terms: 3h + -3h = 0 -26 + -5h = -6 + 0 -26 + -5h = -6 Add '26' to each side of the equation. -26 + 26 + -5h = -6 + 26 Combine like terms: -26 + 26 = 0 0 + -5h = -6 + 26 -5h = -6 + 26 Combine like terms: -6 + 26 = 20 -5h = 20 Divide each side by '-5'. h = -4 Simplifying h = -4
| -5(2x+2y)=(x+3y) | | 1x/5=9/10 | | X-y=z^2 | | x-32=12.6 | | -9x+-63=9 | | 3y=-33 | | -9x+-63=-8 | | 20y+5+3+8+3-6=100000000y+9+4+8-3-4 | | -3(n+7)=-6n+3 | | 15+12=3x-9x | | -3.4=5.1+1.7y | | 60-2x=4x-80 | | 20y+10-15=19y-100 | | 8(d-85)=24 | | 2x^3+5x^2=32+80 | | -2h+16=3h-6 | | -1=-7y+14 | | 4/3e^2 | | -0.56(a+8)=2.8 | | 4(3-x)+2x=-4 | | -2x-5c-4=2x+12-x | | -7(x-5)=42 | | -12m+16=-5m-19 | | 2(-4+k)=-16 | | 8x+4+42+6y=180 | | 2xy(x)= | | 24-6x=-3(8-2x) | | 5x-2(3-4x)=(x-4)-26 | | X^4+3x^2+6=0 | | 16x^2+0=131 | | 71=4x+50-x | | 3t+3=5t+-7 |